Cropping Systems Mediate Carbon and Nitrogen Substrate Effects on Soil Carbon Dioxide and Nitrous Oxide Emissions - Li, Yuan; Liu, Wenwen; Li, Ying; Ge, Tida; Guan, Tongtong; Kim, Dong-Gill; Liang, Guopeng; Shurpali, Narasinha; Bhattarai, Hem Raj; Virkajärvi, Perttu; Siddique, Kadambot H. M.; Shen, Yuying (Springer Nature, 2026)
Agricultural management practices fundamentally influence soil greenhouse gas emissions, yet the mechanisms governing these emissions across different cropping systems remain incompletely understood. This study investigated how carbon (C) substrates and nitrogen (N) additions regulate carbon dioxide (CO2) and nitrous oxide (N2O) emissions in soils from contrasting agricultural systems. Using a factorial design, we examined the effects of C substrates (glucose, citric acid, glutamine) and N addition (KNO3) on greenhouse gas emissions from soils under three-year continuous wheat (Triticum aestivum) or lucerne (Medicago sativa) cultivation. Lucerne soils showed consistently higher N2O emissions (0.42 ± 0.04 nmol m–2 s–1) compared to wheat soils (0.35 ± 0.03 nmol m–2 s–1). CO2 emissions showed substrate-specific responses, with glutamine treatment yielding the highest emissions (1.35 ± 0.12 µmol m–2 s–1), followed by citric acid (1.12 ± 0.09 µmol m–2 s–1) and glucose (0.98 ± 0.08 µmol m–2 s–1), all significantly exceeding the water control (0.82 ± 0.07 µmol m–2 s–1). Structural equation modeling revealed that substrate effects were mediated through distinct pathways in each system, with iron availability and enzyme activities explaining 37% and 29% of emission variations in lucerne and wheat soils, respectively. Network analysis suggested strong correlations between N2O emissions and soil iron fractions (r = 0.64–0.69) in both systems. Citric acid enhanced N2O emissions by 31% through pH-mediated effects on denitrification, while glucose and glutamine suppressed emissions by 24% and 18%, respectively, through enhanced N immobilization. The contrasting responses between systems reflected fundamental differences in microbial resource utilization strategies, with lucerne soils showing stronger coupling between C and N cycling processes (path coefficient = 0.45). These findings suggest that greenhouse gas mitigation strategies should consider both cropping system legacy effects and substrate-specific response patterns. System-specific approaches targeting both C input quality and N availability may offer effective pathways for emission reduction in agricultural soils.
Keywords: enzymatic activities; crop rotation; priming effect; organic acids